Achieving the dual goals of biomass production and soil rehabilitation with sown pasture on marginal cropland: Evidence from a multi-year field experiment in Northeast Inner Mongolia - Xu, Lijun; Li, Da; Wang, Di; Ye, Liming; Nie, Yingying; Fang, Huajun; Xue, Wei; Bai, Chunli; Van Ranst, Eric (Frontiers in Plant Science, 2022)
Grassland is the primary land use in China but has experienced severe degradation in recent decades due to overgrazing and conversion to agricultural production. Here, we conducted a field experiment in northeastern Inner Mongolia to test the effectiveness of sown pastures in lowering the grazing pressure on grasslands and raising the quality of marginal soils. Alfalfa and smooth bromegrass monocultures and mixture were sown in a marginal cropland field in Hulunber in June 2016. Biomass productivity, soil physicochemical, and biological properties were monitored annually from 2016 to 2020. The results showed that the marginal cropland soil responded consistently positively to sown pastures for major soil properties. Soil organic carbon (SOC) and total nitrogen (TN) increased by 48 and 21%, respectively, from 2016 to 2020 over the 0-60 cm soil depth range. Soil microbes responded proactively too. The soil microbial biomass C (SMBC) and N (SMBN) increased by 117 and 39%, respectively, during the period of 2016-2020. However, by the end of the experiment, the soil of a natural grassland field, which was included in the experiment as a control, led the sown pasture soil by 28% for SOC, 35% for TN, 66% for SMBC, and 96% for SMBN. Nevertheless, the natural grassland soil’s productive capacity was inferior to that of the sown pasture soil. The average aboveground biomass productivity of sown pastures was measured at 8.4 Mg ha-1 in 2020, compared to 5.0 Mg ha-1 for natural grassland, while the root biomass of sown pastures was averaged at 7.5 Mg ha-1, leading the natural grassland by 15%. Our analyses also showed that the sown pastures’ biomass productivity advantage had a much-neglected potential in natural grassland protection. If 50% of the available marginal cropland resources in Hulunber under the current environmental protection law were used for sown pastures, the livestock grazing pressure on the natural grasslands would decrease by a big margin of 38%. Overall, these results represent systematic empirical and analytical evidence of marginal cropland soil’s positive responses to sown pastures, which shows clearly that sown pasture is a valid measure both for soil rehabilitation and biomass production.